N‐heterocyclic carbene (NHC) boosted photoluminescence: Synthesis, structures, and photophysical properties of bpy/phen‐Au(III)‐NHC complexes. (16th August 2022) - Maity, Lakshmikanta; Barik, Sahadev; Biswas, Raju; Natarajan, Ramalingam; Dinda, Joydev
Abstract : Herein, we first present synthesis, structures, luminescent properties, and electrochemistry of gold(III)‐N‐heterocyclic carbene (NHC) complexes fasten with 2, 2′‐bipyridine (bpy) or 1, 10′‐phenanthroline (phen). Starting from the proligand 3‐[pyridin‐3‐yl]imidazo[1, 5‐ a ]pyridin‐4‐ylium hexafluorophosphate (1 ·HPF6 ), two novel complexes, namely, [Au(1 )(bpy)Cl][PF6 ]2 (2 ) and [Au(1 )2 (phen)][PF6 ]3 (3 ), have been synthesized and characterized by several spectroscopic techniques. Finally, the solid‐state structures of 2, 3, and precursors [Au(bpy)Cl2 ][PF6 ] and [Au(phen)Cl2 ][PF6 ] have been determined by single‐crystal X‐ray diffraction studies. The absorption, emission, and lifetime properties of 2 and 3 have been compared with the precursors [Au(bpy)Cl2 ][PF6 ] and [Au(phen)Cl2 ][PF6 ] to observe the influence of NHC. Though the precursors [Au(bpy)Cl2 ][PF6 ] and [Au(phen)Cl2 ][PF6 ] are non‐luminescent, yet complexes 2 and 3 are luminescent. A combination of the chromophoric and π‐acid bpy/phen ligand in Au(III) complexes with the strong σ‐donor NHC ligand significantly enhanced the emission properties of the complexes. The blue emission of 2 and 3 in 390–500 nm regions has been tentatively ascribed to arise from intraligand and metal‐to‐ligand charge transfer (MLCT) transitions; also, partial contributions are expected from hydrogen‐bonding interactions. Cyclic voltammetric studies revealed Au(III) → Au(I) and Au(I) → Au(0) reductions at ~  −0.35 to ‐0.29 V and ~  −1.20 to ‐1.15 V, and the potentials are compared with precursors. Abstract : Synthesis, characterization, luminescence, and electrochemical properties of Au(III)‐NHC fasten with 2, 2′‐bipyridine (bpy) or 1, 10′‐phenanthroline (phen) are reported. Structural diversity and influence of NHC ligand on photoluminescence are also described.